Co-doped layered oxide positive electrode material and sulfide all-solid-state battery

By adopting anion and cation co-doping technology in layered oxide positive electrode materials, the mechanical instability and electrochemical instability of layered oxide positive electrode materials in lithium-ion batteries are solved, and the rate performance and cycling performance of all-solid-state batteries are significantly improved.

CN119812289AActive Publication Date: 2025-04-11ZHEJIANG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510295494.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-11
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

Laminated oxide positive electrode materials have mechanical instability, electrochemical instability and internal structural instability of the body phase in lithium-ion batteries, resulting in unsatisfactory power density and service life.

Method used

Modified layered oxides co-doped with anion and cations are used to eliminate the residual alkali on the surface through the pickling and sintering process and realize doping to build a body phase with uniform lithium ion transport, stable structure and high mechanical strength, and stable interface surface.

Benefits of technology

It significantly improves the rate performance and cycling performance of all-solid-state batteries, improves the mechanical stability and electrochemical stability of the layered oxide positive electrode, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812289A_ABST
    Figure CN119812289A_ABST
Patent Text Reader

Abstract

The invention discloses a co-doped layered oxide positive electrode material and sulfide all-solid-state battery, and belongs to the technical field of batteries, modified layered oxide is anion and cation co-doped layered oxide, the chemical general formula is Li < 1-a > Ni < x > Co < y > Mn < 1-x-y > MaO < 2-b > F , a < = 0.08, 0 < = x < = 1, 0 < = y < = 1, and x and y are not 0 and 0 lt at the same time; b < = 0.2; m is selected from at least one of Al, Si, Zr, Ti, Sn, Sb and Ta and comes from a fluorine-containing weak acid material. According to the invention, a bulk phase with uniform lithium ion transmission and a stable structure and a surface with high mechanical strength and a stable interface are constructed, and the rate capability and the cycle performance of the all-solid-state battery are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a co-doped layered oxide positive electrode material and a sulfide all-solid-state battery. Background Art

[0002] With the rapid rise of electric vehicles and large-scale energy storage, lithium-ion batteries, as the most critical energy storage equipment, have attracted widespread attention, and the demand for their energy density, power density, service life and safety performance is growing. Currently, commercial lithium-ion batteries have safety hazards such as flammability and leakage due to the liquid electrolyte used. The battery may cause fire or explosion accidents due to overcharging, internal short circuits and other reasons, which may cause the electrolyte to overheat. In addition, the energy density of liquid lithium-ion batteries has reached 300 Wh kg −1 bottleneck, and cannot meet the demand for higher energy density of electric vehicles and large-scale energy storage equipment.

[0003] All-solid-state lithium-ion batteries are considered to be the most promising next-generation secondary battery system because they use non-flammable, high-temperature-resistant, non-volatile solid electrolytes that have higher safety performance and energy density than liquid lithium-ion batteries. Among them, all-solid-state lithium-ion batteries assembled with high-ionic conductivity and thermally stable sulfide solid electrolytes and high-voltage, high-specific-capacity layered oxide positive electrodes have attracted much attention from the industry and academia.

[0004] However, the power density and service life of sulfide-based all-solid-state lithium batteries assembled with layered oxide materials as positive electrodes are not ideal. There are mainly the following problems: (1) Mechanical instability of layered oxide positive electrodes. During the charge and discharge process, the layered oxide positive electrode material is prone to cracking due to lattice change stress that breaks through the material surface fracture energy limit under high voltage, high current and long cycle conditions, resulting in inactivation of active substances, increased interfacial impedance and a sharp drop in capacity. (2) Layered oxides and sulfide solid electrolytes are (electro)chemically unstable. During the electrochemical process, the high-valent cations (Ni 4+ ,Co 3+ , Mn 4+Sulfide solid electrolytes such as (etc.) and oxygen free radicals or oxygen are prone to oxidize sulfide solid electrolytes, and sulfide electrolytes with a narrow electrochemical window decompose under high pressure to generate electron- and ion-insulating interfacial by-products. The residual lithium compounds on the surface of the positive electrode further promote the occurrence of interfacial side reactions, resulting in the accumulation of insulating by-products at the interface, increasing the lithium ion transport barrier at the interface, and weakening the rate performance and cycling performance of the solid-state battery. (3) The internal structure of the layered oxide material is unstable. During the charge and discharge process of the layered oxide positive electrode material, to relieve the stress related to the lithium ion concentration gradient inside the particles, transition metal ions migrate to the lithium layer and lattice oxygen is lost, forming a spinel and rock salt phase structure that further hinders the lithium ion transport in the lithium layer, ultimately leading to the collapse of the layered oxide positive electrode structure and severe capacity decay. Therefore, it is necessary to improve the layered oxide positive electrode material and the sulfide all-solid-state battery. Summary of the Invention

[0005] The purpose of the present invention is to provide a co-doped layered oxide positive electrode material and a sulfide all-solid-state battery, which construct a uniform lithium ion transport, stable structure in the bulk phase, and high mechanical strength and stable interface on the surface, greatly improving the rate performance and cycling performance of the all-solid-state battery.

[0006] The technical solution adopted by the present invention to achieve the above purpose is as follows: A modified layered oxide, the modified layered oxide is a layered oxide co-doped with cations and anions, and its chemical general formula is Li 1-a Ni x Co y Mn 1-x-y M a O 2-b F b , where 0 < a ≤ 0.08, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, x and y are not both 0, 0 < b ≤ 0.2; M is selected from at least one of Al, Si, Zr, Ti, Sn, Sb, Ta, and comes from a fluorine-containing weak acid material; In the layered oxide co-doped with cations and anions, due to the different solubilities of the doped cations and anions in the lattice structure of the layered oxide, the doped M cations with lower solubility tend to accumulate in the depth of about 3 - 100 nm near the surface, and the ion concentration decreases from the surface to the bulk phase, and the fluorine anions are uniformly distributed inside the bulk phase.

[0007] According to one aspect of the present invention, a preparation method of the above modified layered oxide is provided, including the following steps: S1. Add the powder of the layered oxide and the weak acid solution to deionized water, stir and mix, and carry out an acid-base reaction; there is LiOH and / or Li2CO3 on the surface of the layered oxide powder, S2. Vacuum-dry the mixed solution obtained in step S1 to obtain a powder coated with an inorganic layer containing elements M and F; after calcining the obtained powder coated with an inorganic layer containing elements M and F, a modified layered oxide is obtained.

[0008] In step S1, the weak acid is H c MF d , where 0 < c ≤ 2, 0 < d ≤ 6, and M is a metal cation or a non-metal cation. Further, M is at least one of Al, Si, Zr, Ti, Sn, Sb, Ta; In step S1, the molar ratio of the amount of substance of M cations in the weak acid to the total amount of substance of transition metal elements in the layered oxide is 0.02 - 0.08:1; In step S1, the mass ratio of the layered oxide to deionized water is 1:1 - 10.

[0009] In step S1, the layered oxide, the weak acid solution and deionized water are stirred and mixed, the stirring speed is 200 - 500 rpm, the temperature of the acid-base reaction is 20 - 30 °C, and the time is 5 - 30 h; In step S1, the coating principle is that the weak acid solution can selectively etch the residual lithium compounds LiOH and Li2CO3 on the surface of the layered oxide to form a uniform inorganic coating layer containing elements M and F on the material surface.

[0010] In step S2, the temperature of vacuum drying is 80 - 130 °C, and the drying time is 8 - 24 h; In step S2, the calcination atmosphere is one of oxygen, air and pure argon, the calcination temperature is 200 - 700 °C, the heating rate is 1 - 30 °C / min, and the calcination time is 1 - 20 h.

[0011] With the above technical solution, the acid washing and sintering process can eliminate harmful residual alkali compounds on the surface of the layered oxide material while realizing the co-doping modification of cations and anions. During the sintering process, the different diffusion abilities of M cations and fluoride anions in the layered oxide material are utilized to achieve the enrichment of M cations near the surface and the uniform distribution of fluoride ions inside the bulk phase.

[0012] Introducing M cation-oxygen with a stronger bond than transition metal-oxygen in the near-surface lithium layer can improve the surface mechanical strength of the layered oxide cathode material to enhance the surface fracture energy, inhibit the failure of lithium ion transport caused by mechanical cracking of particles, and at the same time use the strong oxygen-fixing effect of the M cation to effectively prevent the degradation of the near-surface structure of the cathode and the occurrence of interfacial side reactions, reducing the interfacial lithium ion transport energy barrier.

[0013] The highly electronegative fluoride ions introduced into the bulk-structured oxygen layer have a shorter bond length with transition metals than oxygen ions, which helps to expand the lithium layer spacing, alleviate the structural disorder caused by the migration of transition metals to the lithium layer, and achieve uniform and rapid lithium-ion transport in the lithium layer inside the particles.

[0014] The synergistic effect of strong M-O bonding near the surface and highly electronegative fluoride ions in the bulk enables fast lithium-ion transport kinetics in the bulk and at the interface of the layered oxide material, effectively suppressing problems such as particle cracking, structural degradation, and interfacial side reactions that occur under high current and high voltage, and significantly improving the rate performance and cycling performance of all-solid-state lithium batteries.

[0015] According to one aspect of the present invention, there is provided an all-solid-state lithium battery, comprising a positive electrode, a negative electrode, and an intermediate layer electrolyte; the positive electrode includes a positive electrode material, the positive electrode material includes a positive electrode main material, the positive electrode main material includes one or more of Li6PS5Cl, Li 10 GeP2S 12 、Li 10 SnP2S 12 and a modified layered oxide, the modified layered oxide is a layered oxide co-doped with cations and anions, and its chemical general formula is Li 1-a Ni x Co y Mn 1-x-y M a O 2-b F b ,where 0 < a ≤ 0.08, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, x and y are not both 0, 0 < b ≤ 0.2; M is selected from at least one of Al, Si, Zr, Ti, Sn, Sb, Ta, and comes from a fluorine-containing weak acid material; the negative electrode is a lithium-indium alloy; the intermediate layer electrolyte is one of Li6PS5Cl, Li 10 GeP2S 12 、Li 10 SnP2S 12 .

[0016] Preferably, the intermediate layer electrolyte used in the all-solid-state lithium metal battery is Li6PS5Cl.

[0017] Preferably, the positive electrode material further includes a conductive agent and a binder, and the mass ratio of the positive electrode main material, the conductive agent, and the binder is 85-95:3-10:2-5.

[0018] Preferably, the binder is one or more of polyvinylidene fluoride, polyimide, carboxymethyl cellulose, and sodium alginate; Preferably, the conductive agent is one or more of Super P, acetylene black, Ketjen black, conductive carbon black, carbon nanotubes, graphene, and modified graphene; the modified graphene is obtained by carbonizing amino-modified graphene oxide, and the amino-modified graphene oxide is obtained by modifying graphene oxide with 2,2'-diamino-4,4'-bithiazole and / or benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine.

[0019] By adopting the above technical solution, in the positive electrode material, the use of modified graphene as the conductive agent helps to improve the electrochemical performance of the resulting battery, and can significantly improve the first coulombic efficiency of the resulting sodium ion, the positive electrode energy density and the cycle performance.

[0020] This may be because the modified graphene obtained by carbonization of amino-modified graphene oxide helps to form a good conductive network in the obtained positive electrode material, reduce internal resistance and is not easy to polarize, thereby improving the performance of the obtained battery. In particular, the modified graphene oxide is modified by 2,2'-diamino-4,4'-bithiazole and / or benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine. After carbonization, the microstructure of the modified graphene changes, making it more suitable as a sulfur host. At the same time, it has an adsorption effect on lithium polysulfide in the electrochemical process, which can effectively promote the redox reaction kinetics of lithium-sulfur batteries and help reduce the loss of sulfur active substances.

[0021] According to one aspect of the present invention, there is provided a method for preparing modified graphene, comprising the following steps: Graphene oxide (GO) is mixed with NHS (N-hydroxysuccinimide) and EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride), and anhydrous DMF is added under a nitrogen atmosphere, and the mixture is stirred for activation; then, 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine are added, and the mixture is stirred for reaction for 8-24 hours under a nitrogen atmosphere. After the reaction is completed, the solid product is collected by centrifugation, washed with deionized water, and then dried to obtain amino-modified graphene oxide; the obtained amino-modified graphene oxide is carbonized to obtain modified graphene.

[0022] Preferably, the mass ratio of GO to NHS is 1:1-3; Preferably, the mass ratio of NHS (N-hydroxysuccinimide) to EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) is 1:0.5-2; Preferably, the mass volume ratio of GO to anhydrous DMF is 5-15 mg:3 mL; Preferably, the mass ratio of 2,2'-diamino-4,4'-bisthiazole to benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is 0.5-2:0.5-2; Preferably, the mass ratio of GO to 2,2'-diamino-4,4'-bisthiazole is 1:2-20.

[0023] Preferably, the carbonization temperature is 1000-2000 °C and the carbonization time is 1-4 h.

[0024] According to one aspect of the present invention, the cathode material includes a cathode main material, a conductive agent, and a binder. The cathode main material includes a modified layered oxide, which is a layered oxide co-doped with cations and anions, and its chemical general formula is Li 1-a Ni x Co y Mn 1-x-y M a O 2-b F b , where 0 < a ≤ 0.08, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, x and y are not both 0, 0 < b ≤ 0.2; M is selected from at least one of Al, Si, Zr, Ti, Sn, Sb, Ta and comes from a fluorine-containing weak acid material; the conductive agent includes nitrogen-doped porous carbon nanosheets and one or more of Super P, acetylene black, Ketjen black, conductive carbon black, carbon nanotubes, graphene, modified graphene. The modified graphene is obtained by carbonizing amino-modified graphene oxide, and the amino-modified graphene oxide is obtained by modifying graphene oxide with 2,2'-diamino-4,4'-bisthiazole and / or benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine; the nitrogen-doped porous carbon nanosheets are obtained by carbonizing melamine, melamine diamide or melamine cyanurate with arbutin.

[0025] According to an embodiment of the present invention, the cathode material includes a cathode main material, a conductive agent, and a binder. The cathode main material includes a modified layered oxide, which is a layered oxide co-doped with cations and anions, and its chemical general formula is Li 1-a Ni x Co y Mn 1-x-y M a O 2-b F b, where \(0 < a\leq0.08\), \(0\leq x\leq1\), \(0\leq y\leq1\), \(x\) and \(y\) are not both \(0\), and \(0 < b\leq0.2\); \(M\) is selected from at least one of \(Al\), \(Si\), \(Zr\), \(Ti\), \(Sn\), \(Sb\), \(Ta\) and comes from a fluorine-containing weak acid material; the conductive agent includes nitrogen-doped porous carbon nanosheets and modified graphene, and the modified graphene is obtained by carbonizing amino-modified graphene oxide, and the amino-modified graphene oxide is obtained by modifying graphene oxide with 2,2'-diamino-4,4'-bithiazole and / or benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine; the nitrogen-doped porous carbon nanosheets are obtained by carbonizing melamine, melamine diamide or melamine cyanurate with arbutin.

[0026] Preferably, in the conductive agent, the mass ratio of the modified graphene to the nitrogen-doped porous carbon nanosheets is 1:0.15 - 1.

[0027] The preparation method of the nitrogen-doped porous carbon nanosheets is as follows: Disperse melamine, melamine diamide or melamine cyanurate and arbutin in an aqueous ethanol solution to obtain a dispersion. Dry the above dispersion at a temperature of 60 - 85 °C, grind the obtained solid, and then heat it to 350 - 500 °C in a nitrogen atmosphere and keep it for 1 - 3 h; then heat it to 600 - 750 °C and keep it for 1 - 3 h; then heat it to 950 - 1200 °C and keep it for 1 - 3 h. Then naturally cool it to 25 °C to obtain the nitrogen-doped porous carbon nanosheets.

[0028] Among them, ethanol and water in the aqueous ethanol solution are mixed according to a volume ratio of 1:0.5 - 1.5; the mass ratio of melamine, melamine diamide or melamine cyanurate to arbutin is 10 - 30:1; the mass-volume ratio of melamine, melamine diamide or melamine cyanurate to the aqueous ethanol solution is 0.5 - 3 g:10 mL.

[0029] Adopting the above technical solution, in the positive electrode material, adding nitrogen-doped porous carbon nanosheets to the conductive agent can further improve the electrochemical performance of the obtained sulfide all-solid-state battery. Especially when the modified graphene and the nitrogen-doped porous carbon nanosheets are used in combination, the initial Coulomb efficiency, positive electrode energy density and cycle performance of the obtained battery are further improved.

[0030] This may be because, in the nitrogen-doped porous carbon nanosheets, the doping of nitrogen atoms can effectively regulate the charge distribution and increase the electron transfer rate. Moreover, the nitrogen-doped porous carbon nanosheets can provide more active sites and promote electron transfer, thus contributing to improving the electrochemical performance of the obtained battery.

[0031] According to one aspect of the present invention, there is provided the application of the above all-solid-state lithium battery in an electric vehicle.

[0032] Compared with the prior art, the present invention has the following beneficial effects: 1. Provide a modified layered oxide and a method for preparing the modified layered oxide. Based on the elimination of residual lithium compounds and co-doping of anions and cations, a bulk phase with uniform lithium ion transmission and stable structure and a surface with high mechanical strength and stable interface are constructed, which greatly improves the rate performance and cycle performance of all-solid-state batteries. The strong MO bonding introduced near the surface improves the surface mechanical strength and chemical stability, effectively improves the high interface impedance caused by mechanical cracking and accumulation of interface insulation side reaction products of the layered oxide positive electrode under high current and high voltage, and improves the interfacial lithium ion transmission kinetics. The highly electronegative fluoride anions introduced into the oxygen sites inside the bulk phase of the layered oxide material are more strongly bonded to the transition metal ions, inhibiting the migration of the transition metal to the lithium layer to produce a disordered phase with low ion transmission, and expanding the lithium interlayer spacing, alleviating the internal and external lithium concentration gradient of the positive electrode particles during the charge and discharge process. It works synergistically with the strong MO bonding near the surface, thereby improving the structural stability and lithium ion transmission kinetics of the layered oxide positive electrode.

[0033] 2. The all-solid-state lithium battery assembled with the above-mentioned layered oxide positive electrode has the advantages of large charge and discharge capacity, high rate performance and excellent cycle performance under high current.

[0034] 3. The acid-washing and sintering process can simultaneously achieve the elimination of residual alkali on the surface and the co-doping of anions and cations. The preparation process is simple, efficient, and low-cost, meeting the requirements of industrial production, and is expected to greatly promote the large-scale commercialization of layered oxide positive electrode materials.

[0035] 4. In the process of preparing the positive electrode of the all-solid-state lithium battery, the composite positive electrode main material I containing modified peroxide is used, and the conductive agent modified graphene is used in combination, which can significantly improve the first coulomb efficiency, positive electrode energy density and capacity retention rate of the obtained battery. The modified graphene obtained by carbonization treatment of amino-modified graphene oxide helps to form a good conductive network in the obtained positive electrode material, reduce the internal resistance and is not easy to polarize, thereby improving the performance of the obtained battery.

[0036] 5. In the process of preparing the positive electrode of the all-solid-state lithium battery, the use of modified graphene and nitrogen-doped porous carbon nanosheets in the conductive agent in the positive electrode material can further improve the electrochemical performance of the obtained sulfide all-solid-state battery, and further improve the first coulomb efficiency, positive electrode energy density and cycle performance of the obtained battery. This may be because nitrogen-doped porous carbon nanosheets can provide more active sites and promote electron transfer, thereby helping to improve the electrochemical performance of the obtained battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the XRD test result diagram of the positive electrode main material obtained in Example 1; Figure 2 This is the XRD test result diagram of the positive electrode main material obtained in Comparative Example 1; Figure 3 HRTEM image of a particle slice of the layered oxide obtained in Example 1; Figure 4 The HRTEM spectrum element information results of the layered oxide particle slice obtained in Example 1; Figure 5 This is a scanning electron microscope morphology image of the positive electrode sheet of the battery obtained in Example 1 after 150 cycles; Figure 6 This is a scanning electron microscope morphology image of the positive electrode sheet of the battery obtained in Comparative Example 1 after 150 cycles. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] Example 1 Preparation of modified layered oxides S1. Layered oxide LiNi 0.83 Co 0.12 Mn 0.05 O2 powder and weak acid solution are added to deionized water, stirred and mixed to carry out acid-base reaction; LiOH and Li2CO3 are present on the surface of the layered oxide powder, the weak acid is H2SiF6 aqueous solution, and the mass percentage of H2SiF6 is 30wt%.

[0040] S2. The mixed solution obtained in step S1 is dried in vacuum to obtain a powder coated with an inorganic layer containing Si and F elements; and the powder coated with an inorganic layer containing Si and F elements is calcined to obtain a modified layered oxide.

[0041] In step S1, the molar ratio of the amount of non-metallic cation Si in the weak acid to the total amount of transition metal elements in the layered oxide is 0.02: 1; In step S1, the mass ratio of the layered oxide to deionized water is 1:10.

[0042] In step S1, the layered oxide, the weak acid solution and the deionized water are stirred and mixed at a stirring speed of 300 rpm, a temperature of the acid-base reaction of 30°C, and a time of 10 h; In step S2, the vacuum drying temperature is 100°C and the drying time is 12h; In step S2, the calcination atmosphere is air, the calcination temperature is 500°C, the heating rate is 5°C / min, and the calcination time is 10 h.

[0043] The modified layered oxide was prepared according to the above method, and the general chemical formula is Li 0.996 N i0.83 Co 0.12 Mn 0.05 Si 0.00 4F 0.024 O 1.976 , Si comes from H2SiF6; the above-mentioned modified layered oxide is a layered oxide co-doped with anions and cations, the non-metallic cation Si is enriched at a depth of about 3~100 nm near the surface, the ion concentration decreases from the surface to the bulk phase, and the fluoride anions are uniformly distributed inside the bulk phase.

[0044] Preparation of all-solid-state lithium batteries The all-solid-state lithium battery includes a positive electrode, a negative electrode and an intermediate layer electrolyte; the positive electrode includes a positive electrode material, and the positive electrode material includes a positive electrode main material.

[0045] In this embodiment, the modified layered oxide obtained above and Li6PS5Cl are mixed uniformly in a mass ratio of 7:3 to obtain a composite positive electrode main material I, and the composite positive electrode main material I is rolled to obtain a positive electrode film, which is used as a positive electrode material to prepare a positive electrode; Li6PS5Cl was placed in a polyetheretherketone mold and pressed at a pressure of 380 MPA for 5 min to obtain a solid electrolyte sheet. The positive electrode film was placed on one side of the solid electrolyte sheet and pressed at a pressure of 380 MPA for 10 min. The mass ratio of the solid electrolyte sheet to the positive electrode material was 10:1. Finally, a lithium-indium alloy negative electrode with an indium content of 60wt% was placed on the other side and pressed at a pressure of 20 MPA for 1 min to make an all-solid-state lithium battery.

[0046] Example 2 The difference between this embodiment and embodiment 1 is that: In the preparation of the modified layered oxide, in step S1, the molar ratio of the amount of the non-metallic cation Si in the weak acid to the total amount of the transition metal element in the layered oxide is 0.04: 1; the prepared modified layered oxide has a chemical formula of Li 0.992 N i0.83 Co 0.12 Mn 0.05 Si 0.008 F 0.048 O 1.952 .

[0047] The other conditions and steps were the same.

[0048] Example 3 The difference between this embodiment and embodiment 1 is that: In the preparation of the modified layered oxide, in step S1, the layered oxide is LiNi0.6 Co 0.2 Mn 0.2 O2; the molar ratio of the amount of non-metallic cation Si in the weak acid to the total amount of transition metal elements in the layered oxide is 0.02:1; the modified layered oxide obtained has a general chemical formula of Li 0.996 N i0.6 Co 0. 2 Mn 0.2 Si 0.004 F 0.024 O 1.976 .

[0049] The other conditions and steps were the same.

[0050] Example 4 The difference between this embodiment and embodiment 1 is that: In the preparation of all-solid-state lithium batteries, the positive electrode materials include positive electrode main material, conductive agent and binder.

[0051] In this embodiment, modified layered oxide and Li6PS5Cl are mixed uniformly in a mass ratio of 7: 3 to obtain a composite positive electrode main material I; the conductive agent is modified graphene, and the binder is polyvinylidene fluoride; the mass ratio of the positive electrode main material, the conductive agent, and the binder is 90:3:3, and the composite positive electrode main material I, the conductive agent, and the binder are mixed, and then ball milled at 200rpm for 1h, and then rolled to obtain a positive electrode film, which is used as a positive electrode material to prepare a positive electrode. The solid electrolyte sheet, the negative electrode, and other conditions and steps are the same as those in Example 1.

[0052] Wherein, the preparation method of the modified layered oxide is the same as that in Example 1.

[0053] The preparation method of modified graphene is as follows: GO was prepared by the Hummer method. GO was then mixed with NHS and EDC, and anhydrous DMF was added under a nitrogen atmosphere for stirring and activation. Then, 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine were added, and the mixture was stirred for 12 hours under a nitrogen atmosphere. After the reaction, the solid product was collected by centrifugation, washed with deionized water, and then dried to obtain amino-modified graphene oxide. The obtained amino-modified graphene oxide was carbonized to obtain modified graphene.

[0054] The mass ratio of GO to NHS is 1:2; The mass ratio of NHS to EDC was 1:1; The mass volume ratio of GO to anhydrous DMF was 10 mg:3 mL; The mass ratio of 2,2'-diamino-4,4'-bithiazole to benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is 1:1; The mass ratio of GO to 2,2'-diamino-4,4'-bithiazole was 1:8.

[0055] The temperature of carbonization treatment is 1400℃ and the carbonization time is 2h.

[0056] Example 5 The difference between this embodiment and embodiment 1 is that: In the preparation of all-solid-state lithium batteries, the positive electrode materials include positive electrode main material, conductive agent and binder.

[0057] In this embodiment, modified layered oxide and Li6PS5Cl are mixed evenly in a mass ratio of 7:3 to obtain a composite positive electrode main material I; the conductive agent is modified graphene, and the binder is polyvinylidene fluoride; the mass ratio of the composite positive electrode main material I, the conductive agent, and the binder is 90:5:3.

[0058] Wherein, the preparation method of the modified layered oxide is the same as that of Example 1; The preparation method of modified graphene is the same as that of Example 4.

[0059] The other conditions and steps were the same.

[0060] Example 6 The difference between this embodiment and embodiment 1 is that: In the preparation of all-solid-state lithium batteries, the positive electrode materials include positive electrode main material, conductive agent and binder.

[0061] In this embodiment, modified layered oxide and Li6PS5Cl are uniformly mixed in a mass ratio of 7:3 to obtain a composite positive electrode main material I; the conductive agent is modified graphene, and the binder is polyvinylidene fluoride; the mass ratio of the composite positive electrode main material I, the conductive agent, and the binder is 90:7:3.

[0062] Wherein, the preparation method of the modified layered oxide is the same as that of Example 1; The preparation method of modified graphene is the same as that of Example 4.

[0063] The other conditions and steps were the same.

[0064] Example 7 The difference between this embodiment and embodiment 1 is that: In the preparation of all-solid-state lithium batteries, the positive electrode materials include positive electrode main material, conductive agent and binder.

[0065] In this embodiment, modified layered oxide and Li6PS5Cl are mixed evenly in a mass ratio of 7:3 to obtain a composite positive electrode main material I; the conductive agent is modified graphene, and the binder is polyvinylidene fluoride; the mass ratio of the composite positive electrode main material I, the conductive agent, and the binder is 90:5:3.

[0066] Wherein, the preparation method of the modified layered oxide is the same as that of Example 1; Preparation method of modified graphene Compared with Example 4, the mass ratio of 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is 1.5:0.5; the mass ratio of GO to 2,2'-diamino-4,4'-bithiazole is 1:12.

[0067] The other conditions and steps were the same.

[0068] Example 8 The difference between this embodiment and embodiment 1 is that: In the preparation of all-solid-state lithium batteries, the positive electrode materials include positive electrode main material, conductive agent and binder.

[0069] In this embodiment, modified layered oxide and Li6PS5Cl are mixed evenly in a mass ratio of 7:3 to obtain a composite positive electrode main material I; the conductive agent is modified graphene, and the binder is polyvinylidene fluoride; the mass ratio of the composite positive electrode main material I, the conductive agent, and the binder is 90:5:3.

[0070] Wherein, the preparation method of the modified layered oxide is the same as that of Example 1; Preparation method of modified graphene Compared with Example 4, the mass ratio of 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is 0.5:1.5; the mass ratio of GO to 2,2'-diamino-4,4'-bithiazole is 1:4.

[0071] The other conditions and steps were the same.

[0072] Example 9 The difference between this embodiment and embodiment 1 is that: In the preparation of all-solid-state lithium batteries, the positive electrode materials include positive electrode main material, conductive agent and binder.

[0073] In this embodiment, modified layered oxide and Li6PS5Cl are uniformly mixed in a mass ratio of 7:3 to obtain a composite positive electrode main material I; the conductive agent includes modified graphene and nitrogen-doped porous carbon nanosheets, the mass ratio of modified graphene and nitrogen-doped porous carbon nanosheets is 1:0.2, and the binder is polyvinylidene fluoride; the mass ratio of the composite positive electrode main material I, the conductive agent, and the binder is 90:3.6:3.

[0074] Wherein, the preparation method of the modified layered oxide is the same as that of Example 1; The preparation method of modified graphene is the same as that of Example 4.

[0075] The preparation method of nitrogen-doped porous carbon nanosheets is as follows: Melamine cyanurate and arbutin are dispersed in an aqueous solution of ethanol and ultrasonically treated for 10 minutes to obtain a uniformly mixed dispersion. In the aqueous ethanol solution, ethanol and water are mixed in a volume ratio of 1:1; the mass ratio of melamine cyanurate to arbutin is 20:1; the mass volume ratio of melamine cyanurate to the aqueous ethanol solution is 1g:10mL. The above dispersion is dried at 75°C, and the obtained solid is ground and heated to 450°C at a rate of 5°C / min in a nitrogen atmosphere, and kept warm for 2h; then continue to heat to 650°C at a rate of 5°C / min, and keep warm for 3h; then continue to heat to 1000°C at a rate of 5°C / min, and keep warm for 3h. Then naturally cool to 25°C to obtain nitrogen-doped porous carbon nanosheets.

[0076] The other conditions and steps were the same.

[0077] Example 10 The difference between this embodiment and embodiment 1 is that: In the preparation of all-solid-state lithium batteries, the positive electrode materials include positive electrode main material, conductive agent and binder.

[0078] In this embodiment, modified layered oxide and Li6PS5Cl are uniformly mixed in a mass ratio of 7:3 to obtain a composite positive electrode main material I; the conductive agent includes modified graphene and nitrogen-doped porous carbon nanosheets, the mass ratio of modified graphene and nitrogen-doped porous carbon nanosheets is 1:0.4, and the binder is polyvinylidene fluoride; the mass ratio of the composite positive electrode main material I, the conductive agent, and the binder is 90:4.2:3.

[0079] Wherein, the preparation method of the modified layered oxide is the same as that of Example 1; The preparation method of modified graphene is the same as that of Example 4; The preparation method of nitrogen-doped porous carbon nanosheets is the same as that in Example 9.

[0080] The other conditions and steps were the same.

[0081] Comparative Example 1 The difference between this comparative example and Example 1 is that: The preparation of modified layered oxide is omitted and unmodified layered oxide LiNi is directly used. 0.83 Co 0.12 Mn 0.05 O2 preparation of all-solid-state lithium batteries.

[0082] The other conditions and steps were the same.

[0083] Comparative Example 2 The difference between this comparative example and Example 1 is that: In the preparation of all-solid-state lithium batteries, the positive electrode materials include positive electrode main material, conductive agent and binder.

[0084] The modified layered oxide and Li6PS5Cl were uniformly mixed in a mass ratio of 7:3 to obtain a composite positive electrode main material I; the conductive agent was modified graphene, and the binder was polyvinylidene fluoride; the mass ratio of the composite positive electrode main material I, the conductive agent, and the binder was 90:3:3.

[0085] Wherein, the preparation method of the modified layered oxide is the same as that in Example 1.

[0086] Preparation method of modified graphene Compared with Example 4, benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is replaced by an equal mass of 2,2'-diamino-4,4'-bithiazole.

[0087] The other conditions and steps were the same.

[0088] Comparative Example 3 The difference between this comparative example and Example 1 is that: In the preparation of all-solid-state lithium batteries, the positive electrode materials include positive electrode main material, conductive agent and binder.

[0089] The modified layered oxide and Li6PS5Cl were uniformly mixed in a mass ratio of 7:3 to obtain a composite positive electrode main material I; the conductive agent was modified graphene, and the binder was polyvinylidene fluoride; the mass ratio of the composite positive electrode main material I, the conductive agent, and the binder was 90:3:3.

[0090] Wherein, the preparation method of the modified layered oxide is the same as that in Example 1.

[0091] Preparation method of modified graphene Compared with Example 4, 2,2'-diamino-4,4'-bithiazole is replaced by an equal mass of benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine.

[0092] The other conditions and steps were the same.

[0093] Comparative Example 4 The difference between this comparative example and Example 1 is that: In the preparation of all-solid-state lithium batteries, the positive electrode materials include positive electrode main material, conductive agent and binder.

[0094] The modified layered oxide and Li6PS5Cl were uniformly mixed in a mass ratio of 7:3 to obtain a composite positive electrode main material I; the conductive agent was graphene, and the binder was polyvinylidene fluoride; the mass ratio of the composite positive electrode main material I, the conductive agent, and the binder was 90:3:3.

[0095] Wherein, the preparation method of the modified layered oxide is the same as that in Example 1.

[0096] The other conditions and steps were the same.

[0097] Test example XRD test The positive electrode main materials obtained in Example 1 and Comparative Example 1 were subjected to powder X-ray diffraction (XRD) tests. The results are shown in Figure 1 and Figure 2 ; The XRD refinement results of the obtained layered oxide positive electrode are shown in Table 1.

[0098] Table 1 XRD refinement results of the positive electrode main materials obtained in Example 1 and Comparative Example 1

[0099] Combination Figure 1 and Figure 2 The XRD characteristic peaks of the composite positive electrode material I containing modified layered oxide obtained in Example 1 are consistent with those of the positive electrode material obtained in Comparative Example 1, and no obvious impurity peaks are observed. In addition, the diffraction peaks at (006) / (102) and (018) / (110) are obviously split, indicating that the modification does not affect the layered structure of the layered oxide.

[0100] The refined data in Table 1 show that the a-axis value of the composite positive electrode main material I containing modified layered oxides decreases and the c-axis value increases, proving that the doped F ions effectively bond strongly with the transition metal to shorten the a-axis and expand the lithium interlayer spacing.

[0101] HRTEM characterization The modified layered oxide material particles obtained in Example 1 were cut and thinned using a focused ion beam, and the thinned particle sheets were transferred to a high-resolution transmission electron microscope for observation, and the Ni, Co, Mn, O, F, and Si element information of the particle sheets were collected using energy dispersive X-ray spectroscopy to intuitively characterize the distribution of the doping elements inside the layered oxide positive electrode particles. The results are shown in Figure 3 and Figure 4 .Depend on Figure 3 and Figure 4 The HRTEM images and energy spectrum analysis of the particle slices show that the Li 0.996 Ni 0.83 Co 0.12 Mn 0.05 Si 0.004 F 0.024 O 1.976 The Si element is enriched near the surface of the particle slice, and the concentration decreases from the surface to the bulk phase. The F element is evenly distributed throughout the particle, which proves the element distribution characteristics of the modified material.

[0102] Electrochemical testing Electrochemical tests were performed on the batteries prepared in Examples 1-10 and Comparative Examples 1-4, respectively.

[0103] The constant current charge and discharge test and cycle life test of the battery are realized by Xinwei CT4000, and the voltage and electrochemical impedance test of the cyclic voltammetry test are realized by Chenhua CHI760D electrochemical workstation.

[0104] For the batteries obtained in Examples 1-10 and Comparative Examples 1-4, the first charge and discharge capacity was tested at a 50C rate and the first coulombic efficiency was calculated. The results of the first coulombic efficiency test are shown in Table 2.

[0105] Table 2 The first coulombic efficiency test results of each embodiment and comparative example

[0106] Referring to the data in Table 2, the first coulombic efficiencies of the batteries obtained in Examples 1-3 are not much different, which shows that when preparing the modified layered oxide, LiNi 0.83 Co 0.12 Mn 0.05 O2 or LiNi 0.6 Co 0.2 Mn 0.2 O2 has little effect on the first coulombic efficiency of the obtained all-solid-state lithium battery. Compared with Example 1, the first coulombic efficiency of the battery obtained in Example 2 is improved. It can be seen that when the composite positive electrode main material I containing modified layered oxide is used to prepare the positive electrode of the all-solid-state lithium battery, the increase in the content of modified layered oxide in the composite positive electrode main material I is helpful to improve the first coulombic efficiency of the obtained all-solid-state lithium battery.

[0107] Compared with Comparative Example 1, the first coulombic efficiency of the battery obtained in Example 1 is increased by 6.7%. It can be seen that, compared with the unmodified layered oxide, the use of the composite positive electrode main material I containing the modified layered oxide to prepare the positive electrode of the all-solid-state lithium battery can greatly improve the first coulombic efficiency of the obtained battery.

[0108] Compared with Example 1, the first coulombic efficiency of the batteries obtained in Examples 4-10 and Comparative Examples 2-4 increased by 8.1%, 9.6%, 11.0%, 5.8%, 6.8%, 13.6%, 14.6%, 5.3%, 6.4% and 2.8%, respectively. Compared with Comparative Example 4, the first coulombic efficiency of the batteries obtained in Examples 4-10 and Comparative Examples 2-3 increased by 5.2%, 6.5%, 7.9%, 2.9%, 3.9%, 10.4%, 11.5%, 2.4% and 3.4%, respectively. It can be seen that in the process of preparing the positive electrode of the all-solid-state lithium battery, the composite positive electrode main material I containing modified peroxide is used, and the conductive agent modified graphene is used to improve the first coulomb efficiency of the obtained battery, especially in the process of preparing the modified graphene, when the mass ratio of 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is 1:1, the first coulomb efficiency of the obtained battery can be significantly improved. The first coulomb efficiency of the battery obtained in Example 4-6 is on an upward trend. It can be seen that in the process of preparing the positive electrode of the all-solid-state lithium battery, increasing the amount of modified graphene used as a conductive agent within a certain range is helpful to improve the first coulomb efficiency of the obtained battery.

[0109] Combined with the data of Example 4 and Examples 7-8, it can be seen that the use of 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine in combination to modify graphene oxide, and the obtained modified graphene is used to prepare an all-solid-state lithium battery, the usage ratio of the two has an impact on the first coulombic efficiency of the obtained all-solid-state lithium battery. When the two are used in combination, the amounts of 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine are equivalent, and the first coulombic efficiency of the obtained all-solid-state lithium battery is more significantly improved than that of using graphene as a conductive agent. When the amount of 2,2'-diamino-4,4'-bithiazole is relatively high or the amount of benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is relatively high, the first coulombic efficiency of the obtained all-solid-state lithium battery is also improved compared with that of using graphene as a conductive agent, but compared with using equivalent amounts of 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine when modifying graphene oxide, the first coulombic efficiency of the obtained all-solid-state lithium battery is relatively reduced.

[0110] Combined with the data of Comparative Examples 2-3, it can be seen that compared with the modified graphene obtained by modifying graphene oxide using 2,2'-diamino-4,4'-bithiazole alone or benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine alone; 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine are used in combination to modify graphene oxide, and the obtained modified graphene is used for the composite positive electrode main material I and to prepare the positive electrode of the all-solid-state lithium battery, and the first coulombic efficiency of the obtained all-solid-state lithium battery is significantly improved.

[0111] Compared with Example 4, the first coulombic efficiency of the batteries obtained in Examples 9-10 was increased by 5.0% and 6.0%, respectively. It can be seen that in the process of preparing all-solid-state lithium batteries, the use of a composite positive electrode main material I containing modified peroxides and the use of a composite of modified graphene and nitrogen-doped porous carbon nanosheets as a conductive agent can further improve the first coulombic efficiency of the obtained battery; and within a certain range, the first coulombic efficiency of the obtained all-solid-state lithium battery is positively correlated with the amount of nitrogen-doped porous carbon nanosheets.

[0112] For the batteries prepared in Examples 1-10 and Comparative Examples 1-4, the capacity of the batteries was obtained by charging to 4.0V at 0.5C constant current and constant voltage, and discharging to 1.5V at 0.5C. The weight of the battery cell was measured with a balance, and the energy density of the battery cell was calculated. The positive electrode energy density test results are shown in Table 3.

[0113] Table 3 Test results of positive electrode energy density of each embodiment and comparative example

[0114] Referring to the data in Table 3, the positive electrode energy densities of the batteries obtained in Examples 1-3 are not much different, which shows that when preparing the modified layered oxide, LiNi 0.83 Co 0.12 Mn 0.05 O2 or LiNi 0.6 Co 0.2 Mn 0.2 O2 has little effect on the positive electrode energy density of the obtained all-solid-state lithium battery. Compared with Example 1, the positive electrode energy density of the battery obtained in Example 2 is improved. It can be seen that when the composite positive electrode main material I containing modified layered oxide is used to prepare the positive electrode of the all-solid-state lithium battery, the increase in the content of modified layered oxide in the composite positive electrode main material I is helpful to improve the positive electrode energy density of the obtained all-solid-state lithium battery.

[0115] Compared with Comparative Example 1, the first coulombic efficiency of the battery obtained in Example 1 is increased by 18.7%. It can be seen that, compared with the unmodified layered oxide, the positive electrode energy density of the obtained battery can be greatly improved by using the composite positive electrode main material I containing the modified layered oxide to prepare the positive electrode of the all-solid-state lithium battery.

[0116] Compared with Example 1, the positive electrode energy density of the batteries obtained in Examples 4-10 and Comparative Examples 2-4 increased by 10.8%, 13.2%, 15.1%, 6.6%, 9.6%, 16.9%, 19.3%, 5.4%, 7.8% and 4.2%, respectively. Compared with Comparative Example 4, the positive electrode energy density of the batteries obtained in Examples 4-10 and Comparative Examples 2-3 increased by 6.4%, 8.7%, 10.4%, 2.3%, 5.2%, 12.1%, 14.4%, 1.2% and 3.5%, respectively. It can be seen that in the process of preparing the positive electrode of the all-solid-state lithium battery, the composite positive electrode main material I containing modified peroxide is used, and the conductive agent modified graphene is used to improve the positive electrode energy density of the obtained battery, especially in the process of preparing the modified graphene, when the mass ratio of 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is 1:1, the positive electrode energy density of the obtained battery can be significantly improved. The positive electrode energy density of the battery obtained in Example 4-6 is on an upward trend. It can be seen that in the process of preparing the positive electrode of the all-solid-state lithium battery, increasing the amount of modified graphene used as a conductive agent within a certain range is helpful to improve the positive electrode energy density of the obtained battery.

[0117] Combined with the data of Example 4 and Examples 7-8, it can be seen that the use of 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine in combination to modify graphene oxide, and the obtained modified graphene is used to prepare an all-solid-state lithium battery, the usage ratio of the two has an impact on the positive electrode energy density of the obtained all-solid-state lithium battery. When the two are used in combination, the amounts of 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine are equivalent, and the positive electrode energy density of the obtained all-solid-state lithium battery is more significantly improved than that of using graphene as a conductive agent. When the amount of 2,2'-diamino-4,4'-bithiazole is relatively high or the amount of benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is relatively high, the positive electrode energy density of the obtained all-solid-state lithium battery is also improved compared with that of using graphene as a conductive agent, but compared with using equivalent amounts of 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine when modifying graphene oxide, the positive electrode energy density of the obtained all-solid-state lithium battery is relatively reduced.

[0118] Combined with the data of Comparative Examples 2-3, it can be seen that compared with the modified graphene obtained by modifying graphene oxide with 2,2'-diamino-4,4'-bithiazole alone or benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine alone; 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine are used in combination to modify graphene oxide, and the obtained modified graphene is used for the composite positive electrode main material I and to prepare the positive electrode of the all-solid-state lithium battery, and the energy density of the positive electrode of the obtained all-solid-state lithium battery is significantly improved.

[0119] Compared with Example 4, the positive electrode energy density of the battery obtained in Examples 9-10 was increased by 5.4% and 7.6%, respectively. It can be seen that in the process of preparing an all-solid-state lithium battery, the positive electrode main material I containing a modified peroxide is used, and the modified graphene and nitrogen-doped porous carbon nanosheets are used as a conductive agent, which can further improve the positive electrode energy density of the obtained battery; and within a certain range, the positive electrode energy density of the obtained all-solid-state lithium battery is positively correlated with the amount of nitrogen-doped porous carbon nanosheets.

[0120] For the batteries prepared in Examples 1-10 and Comparative Examples 1-4, the cycle performance was tested for 150 cycles using a 1C rate charge / discharge test. The SEM morphology results of the positive electrode sheets obtained in Example 1 and Comparative Example 1 after the cycles are shown in Figure 5 and Figure 6 ;contrast Figure 5 and Figure 6 It can be seen that after the battery obtained in Example 1 is cycled, the morphology of the positive electrode sheet containing the modified layered oxide under the scanning electron microscope shows smaller interface impedance and less interface side reactions and particle cracking, proving that the modified layered oxide improves mechanical stability, interface stability, structural stability and lithium ion transfer kinetics. The capacity retention test results are shown in Table 4.

[0121] Table 4 Capacity retention test results of each embodiment and comparative example after 150 cycles

[0122] Referring to the data in Table 4, the capacity retention rates of the batteries obtained in Examples 1-3 after 150 cycles are similar, which shows that when preparing the modified layered oxide, LiNi 0.83 Co 0.12 Mn 0.05 O2 or LiNi 0.6 Co 0.2 Mn 0.2O2 has little effect on the capacity retention rate of the obtained all-solid-state lithium battery. Compared with Example 1, the capacity retention rate of the battery obtained in Example 2 is improved. It can be seen that when the composite positive electrode main material I containing modified layered oxide is used to prepare the positive electrode of the all-solid-state lithium battery, the increase in the content of modified layered oxide in the composite positive electrode main material I helps to improve the capacity retention rate of the obtained all-solid-state lithium battery.

[0123] Compared with Comparative Example 1, the capacity retention rate of the battery obtained in Example 1 after 150 cycles is increased by 11.2%. It can be seen that, compared with the unmodified layered oxide, the use of the composite positive electrode main material I containing the modified layered oxide to prepare the positive electrode of the all-solid-state lithium battery can greatly improve the capacity retention rate of the obtained battery.

[0124] Compared with Example 1, the capacity retention rates of the batteries obtained in Examples 4-10 and Comparative Examples 2-4 after 150 cycles were increased by 9.8%, 11.2%, 13.2%, 5.8%, 7.4%, 15.4%, 16.7%, 5.9%, 7.3% and 3.8%, respectively. Compared with Comparative Example 4, the capacity retention rates of the batteries obtained in Examples 4-10 and Comparative Examples 2-3 after 150 cycles were increased by 5.8%, 7.1%, 9.1%, 2.0%, 3.5%, 11.2%, 12.5%, 2.1% and 3.4%, respectively. It can be seen that in the process of preparing the positive electrode of the all-solid-state lithium battery, the composite positive electrode main material I containing modified peroxide is used, and it is combined with conductive agent modified graphene, which can significantly improve the capacity retention rate of the obtained battery. The capacity retention rate of the batteries obtained in Examples 4-6 is on an upward trend. It can be seen that in the process of preparing the positive electrode of the all-solid-state lithium battery, increasing the amount of modified graphene as a conductive agent within a certain range is helpful to improve the capacity retention rate of the obtained battery.

[0125] Combined with the data of Example 4 and Examples 7-8, it can be seen that the use of 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine in combination to modify graphene oxide, and the obtained modified graphene is used to prepare an all-solid-state lithium battery, the usage ratio of the two has an effect on the capacity retention rate of the obtained all-solid-state lithium battery after 150 cycles. When the two are used in combination, the amounts of 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine are equivalent, and the capacity retention rate of the obtained all-solid-state lithium battery is more significantly improved compared with the use of graphene as a conductive agent. When the amount of 2,2'-diamino-4,4'-bithiazole is relatively high or the amount of benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is relatively high, the capacity retention rate of the obtained all-solid-state lithium battery is also improved compared with the use of graphene as a conductive agent, but compared with the use of equivalent amounts of 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine when modifying graphene oxide, the capacity retention rate of the obtained all-solid-state lithium battery is relatively reduced.

[0126] Combined with the data of Comparative Examples 2-3, it can be seen that compared with the modified graphene obtained by modifying graphene oxide using 2,2'-diamino-4,4'-bithiazole alone or benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine alone; 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine are used in combination to modify graphene oxide, and the obtained modified graphene is used for the composite positive electrode main material I and to prepare the positive electrode of the all-solid-state lithium battery, and the capacity retention rate of the obtained all-solid-state lithium battery is significantly improved.

[0127] Compared with Example 4, the capacity retention rates of the batteries obtained in Examples 9-10 after 150 cycles were increased by 5.1% and 6.3%, respectively. It can be seen that in the process of preparing all-solid-state lithium batteries, the use of a composite positive electrode main material I containing modified peroxides and the use of a composite of modified graphene and nitrogen-doped porous carbon nanosheets as a conductive agent can further improve the first coulomb efficiency of the obtained battery; and within a certain range, the capacity retention rate of the obtained all-solid-state lithium battery is positively correlated with the amount of nitrogen-doped porous carbon nanosheets used.

[0128] The conventional operations in the operating steps of the present invention are well known to those skilled in the art and will not be described in detail here.

[0129] The above-described embodiments provide a detailed description of the technical solution of the present invention. It should be understood that the above-described embodiments are only specific embodiments of the present invention and are not intended to limit the present invention. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A modified layered oxide, wherein the modified layered oxide is a layered oxide co-doped with anions and cations, and its general chemical formula is Li 1-a Ni x Co y Mn 1-x-y M a O 2-b F b ,in, 0< a≤0.08, 0 ≤x≤1, 0 ≤y≤1, x and y are not 0 at the same time, 0 < b≤0.2; M is selected from at least one of Al, Si, Zr, Ti, Sn, Sb, and Ta, and is derived from a fluorine-containing weak acid material.

2. A method for preparing a modified layered oxide, characterized in that: The following steps are involved: S1. The layered oxide powder and a weak acid solution are added to deionized water, stirred and mixed, and an acid-base reaction is performed; LiOH and / or Li2CO3 are present on the surface of the layered oxide powder, S2. The mixed solution obtained in step S1 is vacuum dried to obtain a powder containing M and F elements and coated with an inorganic layer; the powder containing M and F elements and coated with an inorganic layer is calcined to obtain a modified layered oxide.

3. The method for preparing the modified layered oxide according to claim 2, characterized in that: In step S1, the weak acid is H c MF d , wherein 0< c ≤2, 0 < d≤6, and M is at least one of Al, Si, Zr, Ti, Sn, Sb, and Ta; The molar ratio of the amount of substance of the M cation in the weak acid to the total amount of substance of the transition metal element in the layered oxide is 0.02~0.08:

1.

4. The method for preparing the modified layered oxide according to claim 2, characterized in that: In step S2, the vacuum drying temperature is 80-130°C and the drying time is 8-24h; In step S2, the calcination atmosphere is one of oxygen, air and pure argon, the calcination temperature is 200-700°C, the heating rate is 1-30°C / min, and the calcination time is 1-20 h.

5. An all-solid-state lithium battery, comprising a positive electrode, a negative electrode and an intermediate layer electrolyte; characterized in that: The positive electrode includes a positive electrode material, the positive electrode material includes a positive electrode main material, and the positive electrode main material includes Li6PS5Cl, Li 10 GeP2S 12 , Li 10 SnP2S 12 and one or more of the modified layered oxides, wherein the modified layered oxide is an anion-cation co-doped layered oxide, and its general chemical formula is Li 1-a Ni x Co y Mn 1-x-y M a O 2-b F b , wherein 0< a≤0.08, 0 ≤x≤1, 0 ≤y≤1, x and y are not 0 at the same time, 0 < b≤0.2; M is selected from at least one of Al, Si, Zr, Ti, Sn, Sb, Ta, and is derived from a fluorine-containing weak acid material.

6. The all-solid-state lithium battery according to claim 5, characterized in that: The positive electrode material also includes a conductive agent and a binder, and the mass ratio of the positive electrode main material, the conductive agent, and the binder is 85-95:3-10:2-5; The binder is one or more of polyvinylidene fluoride, polyimide, carboxymethyl cellulose, and sodium alginate; the conductive agent is one or more of Super P, acetylene black, Ketjen black, conductive carbon black, carbon nanotubes, graphene, and modified graphene; the modified graphene is obtained by carbonizing amino-modified graphene oxide, and the amino-modified graphene oxide is obtained by modifying graphene oxide with 2,2'-diamino-4,4'-bithiazole and / or benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine.

7. The all-solid-state lithium battery according to claim 6, characterized in that: The preparation method of the modified graphene comprises the following steps: Graphene oxide is mixed with N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and anhydrous DMF is added under a nitrogen atmosphere, and the mixture is stirred for activation; then, 2,2'-diamino-4,4'-bithiazole and benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine are added, and the mixture is stirred for reaction for 8-24 hours under a nitrogen atmosphere. After the reaction is completed, the solid product is collected by centrifugation, washed with deionized water, and then dried to obtain amino-modified graphene oxide; the obtained amino-modified graphene oxide is carbonized to obtain modified graphene.

8. The all-solid-state lithium battery according to claim 7, characterized in that: The mass ratio of graphene oxide to N-hydroxysuccinimide is 1:1-3; The mass ratio of N-hydroxysuccinimide to 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 1:0.5-2; The mass volume ratio of graphene oxide to anhydrous DMF is 5-15 mg:3 mL.

9. The all-solid-state lithium battery according to claim 7, characterized in that: The mass ratio of 2,2'-diamino-4,4'-bithiazole to benzo[1,2-d:4,5-d']bis(thiazole)-2,6-diamine is 0.5-2:0.5-2; The mass ratio of graphene oxide to 2,2'-diamino-4,4'-bithiazole is 1:2-20.

10. An electric vehicle, characterized in that: An all-solid-state lithium battery comprising any one of claims 5 to 9.

Citation Information

Patent Citations

  • Surface function combination processing method of high-capacity layered oxide positive electrode material

    CN107768610A

  • Anion-cation co-modified lithium-rich manganese-based composite material, preparation method and application

    CN114613959A

  • Monocrystal-like gradient lithium-rich manganese-based layered oxide surface modification method

    CN114639821A

  • Carbon quantum dot coated oxide positive electrode material and preparation method and application thereof

    CN116314655A

  • Coated sodium-ion battery positive electrode material and preparation method thereof, sodium-ion battery and power-related equipment

    CN118610397A